Noise modeling and removal from electrocardiogram signals: a study using wavelet transform with graphical user interface - Al-Qazzaz, Noor Kamal; Buniya, A.; Aldoori, Alaa A.; Mohd Ali, Sawal Hamid; Ahmad, Siti Anom (Penerbit UTHM, 2024)
The electrocardiogram (ECG) is the recording of the electrical potential of the heart versus time. The analysis of ECG signals has been widely used in cardiac pathology to detect heart disease. The ECGs are non-stationary signals which are often contaminated by different types of noises from different sources. In this study, simulated noise models were proposed for the power-line interference (PLI), electromyogram (EMG) noise, base line wander (BW), white Gaussian noise (WGN) and composite noise. For suppressing noises and extracting the efficient morphology of an ECG signal, various processing techniques have been recently proposed. In this paper, wavelet transform (WT) is performed for noisy ECG signals. The graphical user interface (GUI) system is developed for visual representation and adaptive enhancement on noise modeling in ECG-based signal processing. Percentage root mean square difference () was measured between the modeled noisy signals and the samples of the original ECG. Moreover, cross correlation and root mean square error () were performed between the noisy EEG signals and the denoised ones which resulted from WT denoising technique initially to evaluate the effectiveness of the WT denoising technique. The results show that the WT was successfully removed different types of proposed models of noises. This study will help medical doctors, clinicians, physicians, and technicians to eliminate different types of noise. Moreover, the project could be crucial for the process of automatic diagnosis of different heart diseases.